HEALTH PROMOTION BEHAVIORS OF STUDENTS AT INSTITUTE OF PHYSICAL EDUCATION CHON BURI CAMPUS - Lawa, Kanchana; Bhungob, Wat; Getmaro , Chanjaree; Chooratna, Kasem (Academic Journal of Thailand National Sports University, 2019)
The purpeses of this research were to 1) study the health promotion behaviors of students at Institute of Physical Education Chon Buri Campus, 2) compare demographical factors with the health promotion behaviors of these students, and 3) determine the relationships between the perception factor and the health promotion behaviors of the students. The samples consisted of 117 first-to-fourth-year students enrolled at Institute of Physical Education Chon Buri Campus, who were studying in the first semester of the academic year 2016. The research instrument was a questionnaire constructed by the researcher. By means of the questionnaire, germane data were collected between August and September 2017. Using techniques of descriptive statistics, the researcher analyzed the data collected in terms of percentage, mean, and standard deviation by means of applications of a computer software program. Utilizing the independent samples t-test, the researcher tested differences between two groups of variables, while differences among three groups of variables were tested using the one-way analysis of variance (ANOVA) technique. Pearson’s product moment correlation coefficient (PPMCC) method was additionally employed by the researcher. Statistical significance was set at the level of .05. Findings were as follows: The students who differed in the demographical characteristic of gender did not exhibit concomitant differences in health promotion behaviors. The students who differed in the demographical characteristic of age did not evince parallel differences in health promotion behaviors. The students who differed in the demographical characteristics of faculty of enrollment displayed corresponding differences at the statistically significant level of .05. Finally, the perception factor was determined to be correlated with the health promotion behaviors of the students at a low level (r = 0.517).